La Crosse virus: a scoping review of the global evidence. (5th December 2018) - Harding, S.; Greig, J.; Mascarenhas, M.; Young, I.; Waddell, L. A.
Abstract: Urbanisation and climate change are altering the pattern of California serogroup viruses in North America. As La Crosse virus (LACV) is the most pathogenic of the California serogroup, it is important to identify changes in distribution, transmission and pathogenesis. A scoping review (ScR) was prioritised to summarise the global evidence on LACV. A comprehensive search strategy was used, identified references were screened for relevance and relevant articles were characterised. Each step was conducted by two independent reviewers using pre-tested forms. Analysis identified areas of research saturation and gaps. The ScR included 481 research articles that were mostly journal articles (78.2%) conducted in North America (90.9%) from 1969 to 2016. Most evidence focused on epidemiology (44.9%), virus characteristics (25.8%), transmission conditions (18.7%) and pathogenesis of LACV in hosts (18.3%). Fewer studies evaluated the accuracy of diagnostic tests (8.7%), the efficacy of treatments (3.5%), prevention and control strategies (3.1%), the economic burden of infection (0.6%) and social impact (0.2%) of LACV. None of the literature predicted the impact of climate change on LACV, nor were any cases reported in Canada. These findings are intended to guide research to close knowledge gaps and inform evidence-based decisions surrounding activities for the prevention and control of LACV.